Fertility Intention and Related Factors for Having a Second or Third Child Among Childbearing Couples in Shanghai, China - Chenfeng Zhu; Chenfeng Zhu; Chenfeng Zhu; Li Yan; Li Yan; Li Yan; Yang Wang; Yang Wang; Yang Wang; Sifan Ji; Sifan Ji; Sifan Ji; et al. (Frontiers in Public Health, 2022)
Background and PurposeAs the global fertility rate declines, China has issued two and three-child policies in the past 10 years. Therefore, this study serves to evaluate fertility intention rates and related factors in couples intending to have a second child and third child.MethodsA cross-sectional survey was conducted in mainland China from July to August 2021. Couples with one or two children were invited to participate in our study in order to collect information about more than one child fertility intention and the possibly related factors. Odds ratios (ORs) and their corresponding 95% confidence intervals (CIs) were calculated and adjusted for potential confounding factors.ResultsData was collected from a total of 1,026 couples. Among couples with one child, 130 (16.2%) couples had the intention to have a second child. Additionally, only 9.4% of couples with two children desired to have third child. The study revealed large differences in socioeconomic and personal factors between the two groups. For couples with intentions for a second-child, a female age >35 years (adjusted odds ratio, aOR 1.92), a first child's age range from 3 to 6 (aOR 3.12), annual child spending as a percentage of household income >30% (aOR 2.62), and children's educational barriers (aOR 1.55) were associated with lack of intent to have a second child. Similarly, among couples with two children, parents with family financial constraints (aOR 6.18) and children's educational barriers (aOR 4.93) are more likely to have lack of intent to have a third child. Here, we report that government policies encouraging fertility (aOR 0.04) can effectly promote couples to pursue a second or third child.ConclusionOverall, couples with one or two children in Shanghai had a low intention to give birth to a second or third child. In order to increase the birth rates, it is necessary to implement policies to reduce the burden of raising children and provide relief to parent's pressure of rearing a child with increased free time.